2007
DOI: 10.1093/eurpub/ckl259
|View full text |Cite
|
Sign up to set email alerts
|

Weekday but not weekend alcohol consumption before pregnancy influences alcohol cessation during pregnancy

Abstract: Drinking patterns influenced the rate of alcohol cessation: the heavier the alcohol consumption on weekdays, the lower the rate of alcohol cessation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 32 publications
5
49
1
2
Order By: Relevance
“…The prevalence of any alcohol consumption among pregnant women in Europe has been estimated in the range of 23%-54% (Alvik et al, 2006;Donnelly et al, 2008;Göransson et al, 2003;Palma et al, 2007), and some studies report that as many as 23%-30% of women continue to drink after pregnancy recognition (Alvik et al, 2006;Göransson et al, 2003). In the United States, older, more educated, employed, and unmarried women may have a higher prevalence of alcohol use during pregnancy (CDC, 2009;Waterson et al, 1990).…”
mentioning
confidence: 99%
“…The prevalence of any alcohol consumption among pregnant women in Europe has been estimated in the range of 23%-54% (Alvik et al, 2006;Donnelly et al, 2008;Göransson et al, 2003;Palma et al, 2007), and some studies report that as many as 23%-30% of women continue to drink after pregnancy recognition (Alvik et al, 2006;Göransson et al, 2003). In the United States, older, more educated, employed, and unmarried women may have a higher prevalence of alcohol use during pregnancy (CDC, 2009;Waterson et al, 1990).…”
mentioning
confidence: 99%
“…For example, a prevalence rate of less than 5% has been reported in Japan (Tamaki et al, 2008), about 8% in the US (CDC, 2012) and 20% in Russia (Balachova et al, 2012). A higher share of pregnant women consuming alcohol has been found in European countries such as Spain and Norway, where occurrence of 23% has been reported (Alvik et al, 2006b;Palma et al, 2007); the corresponding figure for Denmark is 45% (Nybo-Andersen et al, 2012) and for France 47% (Malet et al, 2006). It should be noted that these studies have used different cut-offs for drinking, such as any drinking at all (Balachova et al, 2012;Nybo-Andersen et al, 2012;Palma et al, 2007), drinking more than 1 standard drink (SD) (Tamaki et al, 2008) or more than one SD in the past 30 days (CDC, 2012).…”
Section: An International Perspective On Alcohol Consumption Before Amentioning
confidence: 99%
“…A higher share of pregnant women consuming alcohol has been found in European countries such as Spain and Norway, where occurrence of 23% has been reported (Alvik et al, 2006b;Palma et al, 2007); the corresponding figure for Denmark is 45% (Nybo-Andersen et al, 2012) and for France 47% (Malet et al, 2006). It should be noted that these studies have used different cut-offs for drinking, such as any drinking at all (Balachova et al, 2012;Nybo-Andersen et al, 2012;Palma et al, 2007), drinking more than 1 standard drink (SD) (Tamaki et al, 2008) or more than one SD in the past 30 days (CDC, 2012). Further, the data collection methods differ between the studies, some using telephone interviews (CDC, 2012;Nybo-Andersen et al, 2012), others questionnaires (Alvik et al, 2006a) and face-to-face interviews (Balachova et al, 2012;Malet et al, 2006;Palma et al, 2007).…”
Section: An International Perspective On Alcohol Consumption Before Amentioning
confidence: 99%
See 1 more Smart Citation
“…As Ernest Abel [23] has noted: 'FAS is not an equal opportunity birth defect'. Studies of maternal alcohol consumption in OECD countries suggest that women from upper socioeconomic groups are more likely to drink alcohol during pregnancy [24][25][26][27][28][29][30][31][32] but have significantly lower rates of FASD than women in lower socioeconomic groups [23]. One recent study has found that women from more socially disadvantaged backgrounds are more likely to either abstain or binge drink during pregnancy, while those who are from more socially advantaged backgrounds are more likely to drink consistently at low to moderate levels [33].…”
Section: Epidemiological Puzzles In Relationships Between Maternal Almentioning
confidence: 99%